The effect of drone strikes on civilian communication: evidence from Yemen. Issue 2 (15th April 2022) - Christia, Fotini; Zoumpoulis, Spyros I.; Freedman, Michael; Yao, Leon; Jadbabaie, Ali
Abstract: Although covert warfare does not readily lend itself to scientific inquiry, new technologies are increasingly providing scholars with tools that enable such research. In this note, we examine the effects of drone strikes on patterns of communication in Yemen using big data and anomaly detection methods. The combination of these analytic tools allows us to not only quantify some of the effects of drone strikes, but also to compare them to other shocks. We find that on average drone strikes leave a footprint in their aftermath, spurring significant but localized spikes in communication. This suggests that drone strikes are not a purely surgical intervention, but rather have a disruptive impact on the local population.